2014
DOI: 10.3899/jrheum.131226
|View full text |Cite
|
Sign up to set email alerts
|

Rilonacept for Gout Flare Prevention in Patients Receiving Uric Acid-lowering Therapy: Results of RESURGE, a Phase III, International Safety Study

Abstract: Weekly subcutaneous administration of rilonacept 160 mg showed no new safety signals. The safety profile was consistent with previous studies. Rilonacept also significantly reduced the risk of gout flares. Clinicaltrials.gov identifier NCT00856206; EudraCT No. 2008-007784-16.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 36 publications
3
45
0
1
Order By: Relevance
“…These findings were derived from a pooled analysis of three randomized double-blind studies aimed to assess the safety and tolerability of different doses of canakinumab in 1026 patients with type 2 diabetes mellitus [109]. Convincing evidence about the safety of IL-1 inhibitors on the risk of Mtb infection is also derived from a phase III study carried out to evaluate treatment with rilonacept in 1315 patients with gout: neither tuberculosis, nor other opportunistic infections were observed during treatment [110].…”
Section: Anti-interleukin-1 Agents and Risk Of Tuberculosismentioning
confidence: 98%
“…These findings were derived from a pooled analysis of three randomized double-blind studies aimed to assess the safety and tolerability of different doses of canakinumab in 1026 patients with type 2 diabetes mellitus [109]. Convincing evidence about the safety of IL-1 inhibitors on the risk of Mtb infection is also derived from a phase III study carried out to evaluate treatment with rilonacept in 1315 patients with gout: neither tuberculosis, nor other opportunistic infections were observed during treatment [110].…”
Section: Anti-interleukin-1 Agents and Risk Of Tuberculosismentioning
confidence: 98%
“…In randomized, controlled trials, both rilonacept and canakinumab have been shown to prevent flares in patients initiating uratelowering therapy (ULT) [4,5]. However, only canakinumab has consistently shown in phase III trials to be effective treatment for acute flares and to reduce the risk of new flares in patients with difficult-to-treat disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…To date, 3 anti−IL-1 biologic agents have been evaluated in patients with gouty arthritis, either in small, open-label, retrospective studies, such as the IL-1 receptor antagonist anakinra [7,35] or in randomized, controlled trials, such as the IL-1 trap rilonacept [5,36] and the anti−IL-1β monoclonal antibody canakinumab [6]. Today, only canakinumab is approved in the European Union for the treatment of adult patients with frequent gouty arthritis attacks (at least 3 in the previous 12 months) in whom NSAIDs and colchicine are contraindicated, are not tolerated, or do not provide an adequate response, and in whom repeated courses of corticosteroids are not appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Rilonacept was well tolerated and was associated with 70.3% fewer gout flares in a multinational phase III study of 1 315 patients. 50 In view of the cost, it will have a make optimal use of the available drugs to improve outcomes for our patients. The research agenda includes the need for local epidemiological data and critical evaluation of our clinical practice as more than 50% of the recommendations in the guidelines are based on level C evidence (opinions of experts, case studies or standards of care).…”
Section: Prophylactic Therapy For the Prevention Of Acute Gout In Patmentioning
confidence: 99%